The broken room - Clines, Peter, 1969- (Blackstone Publishing, 2022)
"You can still owe the dead. Hector was the best of the best. A government operative who could bring armies to a halt and nations to their knees. But when his own country betrayed him, he dropped off the grid and picked up the first of many bottles. Natalie can't remember much of her life before her family brought her to the US, but she remembers the cages. And getting taken away to the Project with dozens of other young children to become part of their nightmarish experiments. That's how she ended up with the ghost of a dead secret agent stuck in her head. And Hector owes Natalie's ghost a big favor. Now Hector and Natalie are on the run from an army of killers sent to retrieve her. Because the people behind the Project are willing to risk almost anything to get Natalie back and complete their experiments."--